Soybean production in eastern and southern Africa and threat of yield loss due to soybean rust caused by Phakopsora pachyrhizi - Murithi, H.M.; Beed, Fenton D.; Tukamuhabwe, Phineas; Thomma, B.P.; Joosten, M.H. (Wiley, 2016)
Soybean is a major source of oil and proteins worldwide. The demand for soybean has increased in Africa, driven by the growing feed industry for poultry, aquaculture and home consumption in the form of processed milk, baked beans and for blending with maize and wheat flour. Soybean, in addition to being a major source of cooking oil, is also used in other industrial processes such as in the production of paints and candle wax. The demand for soybean in Africa so far outweighs the supply, hence the deficit is mainly covered through imports of soybean products such as soybean meal. The area under soybean production has increased in response to the growing demand, a trend that is expected to continue in the coming years. As the production area increases, diseases and insect pests, declining soil fertility and other abiotic factors pose a major challenge. Soybean rust disease, caused by the fungus Phakopsora pachyrhizi, presents one of the major threats to soybean production in Africa due to its rapid spread as a result of the ease by which its spores are dispersed by the wind. Disease control by introducing resistant soybean varieties has been difficult due to the presence of different populations of the fungus that vary in pathogenicity, virulence and genetic composition. Improved understanding of the dynamics of rust ecology, epidemiology and population genetics will enhance the effectiveness of targeted interventions that, in turn, will safeguard soybean productivity.